2007
DOI: 10.1016/j.clon.2006.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy Dosing Part II: Alternative Approaches and Future Prospects

Abstract: This overview follows on from part I, which described the current practices used in chemotherapy dosing and the paucity of scientific evidence to support them. In part II, alternative approaches are discussed, both in terms of scientific rationale and practical application. These include therapeutic drug monitoring, the use of pharmacokinetic-pharmacodynamic relationships, flat-fixed dosing, Bayesian modelling and dose banding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 84 publications
0
24
0
1
Order By: Relevance
“…Traditionally, this has been done by normalizing dose to body surface area. Several studies have shown that this normalization may be inadequate and different pharmacokinetic-and genetic-based methods with mathematical modelling schemes for quantifying and accounting for patient's variability are being explored [126].…”
Section: Critical Factors For An Evidence-based Timing Of G-csf Adminmentioning
confidence: 99%
“…Traditionally, this has been done by normalizing dose to body surface area. Several studies have shown that this normalization may be inadequate and different pharmacokinetic-and genetic-based methods with mathematical modelling schemes for quantifying and accounting for patient's variability are being explored [126].…”
Section: Critical Factors For An Evidence-based Timing Of G-csf Adminmentioning
confidence: 99%
“…Due to the lack of validated alternatives, BSA-based dosing, even imperfect, continues to be the only system in practice. In this context, the pragmatic concept of dose-banding, actually in use in the UK, can be a support to establish a rationalisation of anticancer drugs production, particularly in centres with increased chemotherapy workload [20].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with these anticancer drugs are primarily individualised to patient body surface area, and result in a Abbreviations: ADE, cytosine arabinoside + daunorubicin + etoposide treatment; AML, acute myeloid leukaemia; Ara-C, cytosine arabinoside; BSA, body surface area; CE, capillary electrophoresis; Dnr, daunorubicin; ED, electrochemical detection; Eto, etoposide; FLD, fluorescence detection; HPLC, high pressure liquid chromatography; LIF, laser induced fluorescence; MS, mass spectrometry; PK-PD, pharmacokinetic-pharmacodynamic; RSD, relative standard deviation; SD, standard deviation; SPE, solid phase extraction; THU, tetrahydrouridine; tR, retention time; UV, ultra-violet. high interpatient drug concentration variability in both plasma and leukemic cells [3][4][5][6]. This prompts for population based pharmacokinetic-pharmacodynamic analysis, where relevant covariates such as liver and kidney function, age, sex, concomitant medication, etc.…”
Section: Introductionmentioning
confidence: 99%
“…can be tested for influence on the PK-PD data. It may be possible to individualise future doses more accurately, and potentially eliminate many of the difficulties associated with the solely BSA-based dose adjustments, if statistically significant co-variates are modelled in concert with PK-PD data [6,7]. The ADE treatment has recently been introduced as a standard induction treatment with the AML15 and 17 trials [webA, webB], and no simultaneous bioanalysis of the three drugs in human plasma has yet been described.…”
Section: Introductionmentioning
confidence: 99%